Answer:
When specific values were put for m and n, it was consistent with the theorem.
That is, m is even integer and n is odd integer.
The product m . n is even, as shown below.
The equivalent expression m . n = (2p)(2q + 1) = 2r is true.
Step-by-step explanation
To check for mistake(s) in the proof of the theorem, we assume specific values for m, n, p, q and r.
Let us put
m = 4(An even integer)
n = 7(An odd integer)
p = 2, q = 3. p and q are integers
Then m = 2p = 2 x 2 = 4
n = 2q + 1 = (2 x 3) + 1 = 6 + 1 = 7
Therefore,
m . n = (2p)(2q + 1) = 2r
m . n = 4 x 7 = [(2x2)*(2x3 + 1)]
m . n = 28(2*14). Here r is 14